Does AI-generated Feedback Have Potential Benefit on EFL Writing?: Exploring Students’ Problems and Voice on Using ProWritingAid - Reti Wahyuni; Herlisa Anggraini (English Language Education, Universitas Internasional Batam, 2026)
This study investigates the potential benefits of AI-generated feedback by exploring student perceptions of ProWritingAid, a popular AI-based writing tool. This study utilized a quantitative approach. The data were collected from 38 university-level EFL students in the first semester through a writing task and questionnaire. The findings identify key challenges students face in English writing, including a lack of confidence, infrequent practice, and difficulties with grammar, vocabulary, and coherence. The results also detail students’ current writing strategies, their limited frequency of receiving feedback, and their preferences for actionable, detailed commentary. The questionnaire data reveals that students primarily used ProWritingAid for grammar and style checking, found its feedback easy to interpret and accurate, and reported increased confidence and improved skills after use. This study contributes to understanding the role of AI tools in writing and offers practical insights for educators considering the integration of AI-driven feedback systems.